Synthesis and Characterization of Boron-Doped Photoelectrocatalyst Hybridized with Metal-Organic Frameworks for CO2 Reduction to Ethanol - Atta, Mahmood Riyadh Ali Saleh (2023)
Photoelectrochemical (PEC) CO2 reduction is a promising approach for promoting the sustainability of global development and solving environmental problems. Graphitic carbon nitride (g-C3N4) is commonly used as PEC catalyst, however, it exhibits limitation on electron-hole separation rate as it has relatively large band gap.